The metamorphosis of the Amazon an environmental history of oil extraction in Ecuador - Feichtner, Maximilian Fritz (Cambridge University Press, 2023)
"A compelling study for readers interested in the environmental history of Latin America, this book sheds light on the complex history of the Ecuadorian rainforest and the impact oil development. This title is part of the Flip it Open Programme and may also be available Open Access. Check our website Cambridge Core for details"--
Includes bibliographical references and index
Keywords: Geschichte; Petroleum industry and trade / Environmental aspects / Ecuador; Petroleum industry and trade / Environmental aspects; Umweltschaden; Waldschaden; Tropischer Regenwald; Erdölindustrie; Ecuador; Hochschulschrift